Ang tunay na lalaki ay ___ subverting the toxic masculinity of young FIlipino men and teen subcultures similar to those bred by the Pastor Hokage Bible study groups - Molintas, Isis Vonne R.
In July 2017, the Filipino public was shocked by revelations of the rapid and widespread growth of "Pastor Hokage Bible Study Groups" (PHBSG) - groups curated by young Filipino men, using Facebook as a platform, and formed around sharing and bonding over sexually explicit material.